The Hidden Gem of Yellow Basket: A Study on Consumer Purchase Intention Through TikTok Shop Involved Affiliate Marketing - Michael Caballero; Nestle Ann D. L. Calvadores; Krishalyn Garcia (Research Synergy Foundation, 2024)
This study explores TikTok’s evolving online environment, focusing on the “TikTok Shop” and the less-known TikTok Business Affiliate Program. This study highlights the challenges consumers face in assessing authenticity among influencers in the era of online purchases, considering TikTok’s ever-changing marketing environment. This study analyzed the impact of Involved Affiliate Marketing on consumer purchase intention, emphasizing the creation of authentic connections through the trustworthiness, expertise, and attractiveness of involved affiliate marketing that benefits businesses and organizations. A quantitative methodology was used in this study. The researchers used simple random sampling to identify their respondents, in which the researchers selected and asked three hundred seventy-eight (378) respondents within Metro Manila. The researchers applied the following statistical treatment: Weighted Mean and Simple Linear Regression to analyze the data. In conclusion, the incorporation of involved affiliate marketing in TikTok’s online shop proved to be extremely beneficial for encouraging consumer purchase intentions. Results showed that involved affiliate marketing, with its sub-variables: Expertise, Attractiveness, and Trustworthiness, has a significant effect on the purchasing intention of consumers and that Involved affiliate marketing, with its sub-variables: Expertise and Attractiveness—has a significant effect on the Attitude of consumers, while sub-variable: Trustworthiness—has a significant effect on the norms of consumers.